Anisotropic Crystalline Protein Nanolayers as Multi‐Functional Biointerface for Patterned Co‐Cultures of Adherent and Non‐Adherent Cells in Microfluidic Devices. Issue 1 (27th August 2014) - Rothbauer, Mario; Ertl, Peter; Theiler, Barbara A.; Schlager, Magdalena; Sleytr, Uwe B.; Küpcü, Seta
<x xml:space="preserve">Abstract</x> The spatial arrangement of cells in their microenvironment is known to significantly influence cellular behavior, thus making the control of cellular organization an important parameter of in vitro co‐culture models. However, recent advances in micropatterning co‐culture methods within biochips do not address the simultaneous cultivation of anchorage‐dependent and non‐adherent cells. To address this methodological gap we combine S‐layer technology with microfluidics to pattern co‐cultures to study the cell‐to‐cell and cell‐to‐surface interactions under physiologically relevant conditions. We exploit the unique self‐assembly properties of SbpA and SbsB S‐layers to create an anisotropic protein nanobiointerface on‐chip with spatially‐defined cytophilic (adhesive) and cytophobic (repulsive) properties. While microfluidics control physical parameters such as shear force and flow velocities, our anisotropic protein nanobiointerface regulates the biological aspects of the co‐culture method including biocompatibility, biostability, and affinity to non‐adherent cells. The reliability and reproducibility of our microfluidic co‐culture strategy based on laminar flow patterned protein nanolayers is envisioned to advance in vitro models for biomedical research.